Initial quartz OSL and dust mass accumulation rate investigation of the Kisiljevo loess sequence in north-eastern Serbia. (20th May 2022) - Perić, Zoran M.; Marković, Slobodan B.; Avram, Anca; Timar-Gabor, Alida; Zeeden, Christian; Nett, Janina J.; Fischer, Peter; Fitzsimmons, Kathryn E.; Gavrilov, Milivoj B.
Abstract: The thick and apparently continuous loess-palaeosol sequences in the Vojvodina region of northern Serbia are recognized and well understood as some of the oldest and most complete terrestrial European palaeoclimatic archives. By contrast, there are few published records for loess profiles from other regions in Serbia. Here we address this knowledge gap by investigating an 8 m thick loess sequence exposed near the village of Kisiljevo in north-eastern Serbia, describing the pedostratigraphy and environmental magnetic signatures in detail and placing these within a chronologic framework using quartz optically stimulated luminescence (OSL) on the 4–11 and 63–90 μm size fractions. Our results show dust accumulation over the last c. 32 ka, with substantial primary loess accumulation during the Early Holocene prior to the formation of the modern soil. We applied two age-depth modelling approaches to estimate dust mass accumulation rates: the Bacon.r software and ADmin model. Both yield high accumulation rates, especially during MIS 2, averaging 550–600 g m −2 a −1 which exceed estimates for other investigated loess sequences in the region.